Revisiting Huxley's Island : Advancing pragmatic ideals through a vision of utopia - Zigler, Ronald Lee (Journal of beliefs and values, 2002)
In the final novel of Aldous Huxley, one finds a utopian vision of society with nonetheless many practical curricular and policy implications. In various respects, a close inspection of Huxley's text reveals a close affinity with many of the educational prescriptions of philosopher John Dewey. Huxley, however, spells out in an unmistakable way the thorough interdependence of all socializing forces on the education and development of our youth. In this regard, and most significantly, Huxley does not hesitate to identify the inescapable role of religious or spiritual values in the education of the young-albeit, he advances a highly unconventional vision of religion and the spiritual domain.